Assistência técnica rural em cooperativas agroindustriais: uma proposta de framework para gerar valor aos cooperados produtores de soja no Estado do Rio Grande do Sul - Ferreira, Pedro Henrique Guardiola (Universidade do Vale do Rio dos Sinos, 2021)
In the State of Rio Grande do Sul, agribusiness has great economic and social relevance. The agrarian structure in the State is characterized by a majority of small properties of up to 50 hectares. In this environment, agricultural cooperatives are of great importance as they bring greater profitability to the productive activity of small rural properties. Barriers such as small scale of production and difficulty in accessing technologies are reduced with the presence of these cooperatives. Among the services offered to associated rural producers is technical assistance, which, in addition to aiming at increasing production and productivity with environmental responsibility, also presents itself as an active and articulated contact channel between the cooperative members and the organization's management. This proximity leads to the creation of trust between the cooperative and rural producers, thus being able to contribute to the loyalty process (direction of production), strengthening the organization's economic face. This work aims to evaluate how the technical assistance service is used by agricultural cooperatives to generate value for their members. The research strategy used was design science research, with the researcher acting in the studied reality, understanding the problem, building and testing possible alternatives and solutions for the researched context. Two agricultural cooperatives that industrialize soybeans in Rio Grande do Sul were studied. We sought to understand, through a literature review and focus groups with members of the participating cooperatives' governance and management bodies, how agricultural technical assistance is used as a value creation factor for the cooperative member and vector of loyalty in these organizations. The research describes the service, presents importance, characteristics, perception of members, participation of governance bodies, indicators and results, evolution and future projection, team and structure, and the link between technical assistance and the loyalty of cooperative soy producers. The study brings advances with proposals to improve the scenario with the suggestion of a framework to guide the planning and revisions about the technical assistance service by agricultural cooperatives that industrialize soy.
Keywords: Cooperativa agropecuária; Assistência técnica rural; Criação de valor; Governança corporativa; Fidelização; Agricultural cooperative; Agricultural technical assistance; Value creation; Corporate governance; Loyalty; ACCNPQ::Ciências Sociais Aplicadas::Administração